Composition for artificial solid electrolyte interface layer formation
Patent Information
- Application Number
- CN202580023795.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-05
- Filing Date
- 2025-03-24
- Publication Date
- 2026-10-30
AI Technical Summary
与此相对,为了在负极上形成强度高且稳定的SEI层,进行了在负极上形成人工固体电解质界面(人工SEI)层的尝试,但在得到的涂膜的均匀性、电解液耐性力学强度等耐久性、低锂离子传导性导致的电阻上升、低电子电阻导致的人工固体电解质界面层/隔膜界面处的活性锂生成、厚膜化导致的能量密度降低等方面,仍有改善的余地
[0032]通过使用本发明的人工固体电解质界面层形成用组合物,能够形成均匀、耐久性优异的人工SEI层。而且,通过使用具备该人工SEI层的电极来制作二次电池,可期待二次电池的电池特性的提高。
Smart Images

Figure SMS_13 
Figure SMS_14
Abstract
Description
Technical Field
[0001] This invention relates to compositions for forming artificial solid electrolyte interface layers. Background Technology
[0002] Recently, rechargeable batteries have been used in a wide range of applications, from mobile phones, wireless home appliances, and electric vehicles to drones and satellite base stations, leading to increasing expectations for improved battery performance. In particular, miniaturization, weight reduction, extended operating time, and longer lifespan are common challenges across these applications, and significant efforts are being made to improve them.
[0003] Among them, secondary batteries that are known to charge and discharge by the movement of metal ions between the positive and negative electrodes exhibit high voltage and high energy density; typically, lithium-ion secondary batteries are known. Typical lithium-ion secondary batteries include those in which active materials capable of retaining lithium are introduced into the positive and negative electrodes, and charging and discharging are achieved through the acceptance and donation of lithium ions between the positive and negative active materials.
[0004] Furthermore, lithium metal secondary batteries (also sometimes simply referred to as "lithium secondary batteries") have been developed as rechargeable batteries using lithium metal as the negative electrode. For example, Patent Document 1 discloses a high-energy-density, high-output lithium metal secondary battery that exhibits a volumetric energy density exceeding 1000 Wh / L and a gravimetric energy density exceeding 350 Wh / kg when discharged at a rate of at least 1C at room temperature. In order to achieve such a lithium metal secondary battery, Patent Document 1 discloses the use of a lithium metal negative electrode with a thickness of approximately 10 μm to 20 μm.
[0005] Furthermore, Patent Document 2 discloses a lithium secondary battery comprising a positive electrode, a negative electrode, a separation membrane between them, and an electrolyte. Metal particles are formed on the negative electrode current collector, and during charging, these particles move from the positive electrode to form lithium metal on the negative electrode current collector. Patent Document 2 discloses a lithium secondary battery that solves the problems of lithium metal reactivity and assembly issues, providing a lithium secondary battery with improved performance and lifespan.
[0006] The aforementioned lithium secondary battery is called an anode-free lithium metal secondary battery (hereinafter sometimes simply referred to as an "anode-free battery"). In this battery, lithium ions migrate from the positive electrode during charging and are deposited as metal on the negative electrode, so lithium metal does not need to be used in the negative electrode during manufacturing. Therefore, the amount of lithium used can be minimized, and since no residual lithium is contained in the battery, improvements in safety and energy density can be expected. In addition, corresponding reductions in cost and simplification of the manufacturing process can also be expected.
[0007] Generally, in lithium-ion batteries, during charging, a reaction occurs between active lithium (such as lithium metal or graphitized lithium) and the electrolyte solvent or electrolyte at the negative electrode surface, forming a solid electrolyte interface (SEI). This suppresses the reaction between the active lithium and the electrolyte solvent / electrolyte at the subsequent negative electrode surface, improving coulombic efficiency during charge and discharge, and thus improving the charge-discharge cycle life of the lithium-ion battery. However, in lithium metal rechargeable batteries, the volume of lithium metal, which serves as the negative electrode, changes significantly during charge and discharge. Furthermore, dendritic crystals called lithium dendrites are formed, damaging the SEI layer. Each time this damage occurs, a reaction occurs between the active lithium and the electrolyte solvent / electrolyte, resulting in a decrease in coulombic efficiency and a decrease in discharge capacity retention, thereby deteriorating the charge-discharge cycle life characteristics. In the following explanation, the SEI layer that forms naturally during charging is sometimes referred to as the native SEI layer. In contrast, in order to form a strong and stable SEI layer on the negative electrode, an attempt was made to form an artificial solid electrolyte interface (artificial SEI) layer on the negative electrode. However, the uniformity of the resulting coating and its electrolyte resistance were problematic. There is still room for improvement in areas such as mechanical strength and durability, resistance increase due to low lithium-ion conductivity, active lithium generation at the interface of artificial solid electrolyte layer / membrane due to low electronic resistance, and energy density reduction due to thick film.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Publication No. 2019-517722
[0011] Patent Document 2: Japanese Patent Publication No. 2019-537226 Summary of the Invention
[0012] The problem that the invention aims to solve
[0013] The present invention was made in view of the above-mentioned actual situation, and its object is to provide a composition for forming an artificial solid electrolyte interface layer that can be suitably used to form an artificial solid electrolyte interface layer for constituting the negative electrode of a secondary battery such as an anode-free lithium metal secondary battery.
[0014] Methods for solving problems
[0015] To achieve the above objectives, the inventors conducted repeated and in-depth research and discovered that a composition for forming an artificial solid electrolyte interface layer, comprising graphene oxide or its salt, an olefin-unsaturated carboxylic acid copolymer or its salt, and a solvent comprising water, can form a uniform coating film, provide an artificial SEI layer with excellent durability, and, in secondary batteries made using electrodes comprising this artificial SEI layer, excellent battery characteristics can be obtained, thereby completing the present invention.
[0016] That is, the present invention provides the following composition for forming an artificial solid electrolyte interface layer.
[0017] 1. A composition for forming an artificial solid electrolyte interface layer, comprising: graphene oxide or a salt thereof, an olefin-unsaturated carboxylic acid copolymer or a salt thereof, and a solvent containing water.
[0018] 2. The composition for forming an artificial solid electrolyte interface layer according to claim 1, wherein the salt of the graphene oxide is a lithium salt.
[0019] 3. The composition for forming an artificial solid electrolyte interface layer according to 1 or 2, wherein the salt of the olefin-unsaturated carboxylic acid copolymer is an amine salt, ammonium salt, or lithium salt of an ethylene-(meth)acrylic acid copolymer.
[0020] 4. The composition for forming an artificial solid electrolyte interface layer according to any one of 1 to 3, wherein the graphene oxide contains carboxyl or phenolic hydroxyl groups as surface functional groups, and the oxygen element ratio is 20 to 60 atm.
[0021] 5. The composition for forming an artificial solid electrolyte interface layer according to any one of 1 to 4, wherein the graphene oxide is a single-layer graphene oxide or a multilayer graphene oxide with a thickness of less than 5 nm.
[0022] 6. An artificial solid electrolyte interface layer obtained from the composition for forming an artificial solid electrolyte interface layer as described in any one of 1 to 5.
[0023] 7. The artificial solid electrolyte interface layer according to 6 has a thickness of less than 1 μm.
[0024] 8. A negative electrode for a secondary battery, having an artificial solid electrolyte interface layer as described in 6 or 7 on a substrate.
[0025] 9. The negative electrode for a secondary battery according to claim 8, wherein the substrate is copper foil.
[0026] 10. The negative electrode for a secondary battery according to 8 or 9, which is a negative electrode for a lithium metal secondary battery.
[0027] 11. The negative electrode for a secondary battery according to 10 is a negative electrode for an anodeless battery.
[0028] 12. A secondary battery having a negative electrode for a secondary battery as described in 8 or 9.
[0029] 13. The secondary battery according to 12 is a lithium metal secondary battery.
[0030] 14. The secondary battery according to 13 is an anode-free battery.
[0031] The effects of the invention
[0032] By using the artificial solid electrolyte interface layer forming composition of the present invention, a uniform and durable artificial SEI layer can be formed. Furthermore, by using an electrode having this artificial SEI layer to fabricate a secondary battery, improvements in the battery characteristics of the secondary battery are expected. Detailed Implementation
[0033] The composition for forming an artificial solid electrolyte interface layer of the present invention (also sometimes referred to as "composition for forming an artificial SEI layer" or "composition") comprises graphene oxide or a salt thereof, an olefin-unsaturated carboxylic acid copolymer or a salt thereof, and a solvent comprising water.
[0034] [Graphene oxide or its salts]
[0035] Graphene oxide is a compound formed by the oxidation of graphene. In this invention, the graphene described above includes single-layer graphene or multilayer graphene with 2 to 100 layers. Furthermore, single-layer graphene refers to a sheet of carbon molecules having a single atomic layer of π bonds.
[0036] The aforementioned graphene oxide has oxidized sites in its structure, and these sites are typically incorporating surface functional groups such as carbonyl groups, carboxyl groups, hydroxyl groups, phenolic hydroxyl groups, and epoxy groups. In this invention, from the perspectives of improving the dispersion stability of the composition for forming the artificial solid electrolyte interface layer, enhancing the lithium-ion conductivity of the artificial solid electrolyte interface layer, and reducing salt formation, the surface functional groups preferably contain carboxyl groups or phenolic hydroxyl groups, and more preferably carboxyl groups.
[0037] From the perspectives of water dispersibility, uniform coating properties, mechanical strength, electrolyte resistance, electronic resistance, and lithium-ion conductivity, the oxygen element ratio of the above-mentioned graphene oxide is preferably 20-60 atm%, more preferably 30-50 atm%. The above-mentioned oxygen element ratio can be determined by XPS.
[0038] Furthermore, the aforementioned graphene oxide typically comprises single-layer graphene oxide or multilayer graphene oxide with 2 to 100 layers. From the perspectives of water dispersibility, uniform coating, mechanical strength, electrolyte resistance, electronic resistance, and lithium-ion conductivity, single-layer graphene oxide or multilayer graphene oxide with a thickness of less than 5 nm is preferred.
[0039] Commercially available products can also be used as the aforementioned graphene oxide, such as EMDMillipore (Merck).
[0040] Examples of salts for the aforementioned graphene oxide include lithium salts, sodium salts, potassium salts, cesium salts, amine salts, and ammonium salts. When used in lithium metal secondary batteries or lithium-ion batteries, lithium salts are preferred from the perspective of the lithium purity of the negative electrode in the lithium metal secondary battery or lithium-ion battery, as well as amine salts and ammonium salts formed from low-molecular-weight amines and ammonia that are partially or completely volatilized during the fabrication of the artificial SEI layer.
[0041] Furthermore, the salts of graphene oxide are obtained by using a prescribed base, which neutralizes the surface functional groups such as carboxyl groups and phenolic hydroxyl groups contained in graphene oxide. Examples of such bases include lithium hydroxide, lithium carbonate, lithium bicarbonate, lithium metal, lithium hydride, lithium tert-butoxide, corresponding sodium compounds (converting the lithium portion to sodium), corresponding potassium compounds (converting the lithium portion to potassium), amines, and ammonia. Tertiary amines with a molecular weight of 200 or less and a boiling point of 200°C or less are preferred.
[0042] [Olefin-unsaturated carboxylic acid copolymers or their salts]
[0043] In the above-mentioned olefin-unsaturated carboxylic acid copolymers, the olefin is generally 2 or more carbon atoms, and as an upper limit, it is preferably 8 or less, and particularly preferably 6 or less. Specifically, examples include ethylene, propylene, butene, pentene, hexene, heptene, octene, etc., with ethylene being particularly preferred.
[0044] Examples of unsaturated carboxylic acids include (meth)acrylic acid, maleic acid, and fumaric acid, with (meth)acrylic acid being particularly preferred.
[0045] In addition, as salts of unsaturated carboxylic acids contained in the above copolymers, examples include amine salts, ammonium salts, lithium salts, sodium salts, potassium salts, etc. In the case of lithium metal secondary batteries and lithium-ion batteries, from the perspective of the lithium purity of the negative electrode, amine salts, ammonium salts and lithium salts are preferred, and tertiary amine salts are more preferred.
[0046] Specific examples of the above-mentioned copolymers include amine or ammonium salts of ethylene-(meth)acrylic acid copolymers, amine, ammonium, or lithium salts of propylene-(meth)methacrylic acid copolymers, with amine, ammonium, or lithium salts of ethylene-(meth)acrylic acid copolymers being preferred, and tertiary amine salts of ethylene-(meth)acrylic acid copolymers being more preferred.
[0047] The olefin content in the above copolymer is preferably 60 to 95 moles of structural units from all monomers.
[0048] The proportion of unsaturated carboxylates in the above copolymers is preferably 5 to 50 mol% from all structural units of the monomers, but this does not exclude the inclusion of a portion of unsalted unsaturated carboxylates. The proportion of unsaturated carboxylates is preferably 10 to 30 mol% from all structural units of the monomers.
[0049] Olefin-unsaturated carboxylic acid copolymers or their salts are typically in particulate form. The average particle size of these particles (hereinafter sometimes referred to as copolymer particles) is preferably 1 μm or less, more preferably 500 nm or less, and even more preferably 100 nm or less, taking into account improvements in the dispersibility of graphene oxide or its salts, increased coating area during coating, improved uniformity of coating thickness, reduced ion conductivity, and increased energy density of the resulting secondary battery. Furthermore, there is no particular limitation on the lower limit; from the perspective of uniform particle size control, 1 nm or more is preferred, and more preferably 10 nm or more.
[0050] In this invention, the primary particle size of the copolymer particles is the value measured using the Cole counter method.
[0051] The aforementioned olefin-unsaturated carboxylic acid copolymers or their salts are also available as commercially available products. Examples of such commercially available products include ZAIKTHENE A, ZAIKTHENE A-GH, and ZAIKTHENE L (all manufactured by Sumitomo Seika Co., Ltd.).
[0052] The content of the above-mentioned olefin-unsaturated carboxylic acid copolymer or its salt, expressed as a mass ratio, is preferably 0.1 to 10 relative to the above-mentioned graphene oxide or its salt 1, more preferably 0.2 to 5, further preferably 0.3 to 3, and particularly preferably 0.5 to 2. By including the olefin-unsaturated carboxylic acid copolymer or its salt within the above range, improvements in ionic conductivity, flexibility, mechanical strength, and adhesion to substrates such as copper foil and negative electrode metals generated on the negative electrode are expected.
[0053] In addition, the above-mentioned olefin-unsaturated carboxylic acid copolymers or their salts can be used alone or in combination of two or more.
[0054] [solvent]
[0055] The solvent used in the preparation of the compositions of the present invention includes water, and may include hydrophilic solvents in addition to water. Hydrophilic solvents are organic solvents that are miscible with water in any way, and examples include ethers such as tetrahydrofuran (THF); amides such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methyl-2-pyrrolidone (NMP); ketones such as acetone; alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and tert-butanol; glycol ethers such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, and propylene glycol monomethyl ether; and glycols such as ethylene glycol and propylene glycol. In the present invention, among these hydrophilic solvents, alcohols are preferred, and methanol, ethanol, 1-propanol, and 2-propanol are more preferred, considering improvements in the dispersibility of carbon black, the coating area during coating, and the uniformity of film thickness on the coating surface.
[0056] These solvents can be used alone or in combination of two or more.
[0057] When organic solvents are included, their content is preferably 10% by mass or less, more preferably 5% by mass or less, in terms of solubility and dispersibility in the solution or dispersion of graphene oxide. Furthermore, there is no particular limitation on the lower limit; if the aforementioned improvement effect is low, it is preferable that the solvent contains no organic solvent (i.e., 0% by mass) to reduce environmental pollution risks and equipment costs.
[0058] [Cross-linking agent]
[0059] In the compositions of the present invention, without impairing the effects of the invention, a crosslinking agent that crosslinks with the surface functional groups of the graphene oxide or the olefin-unsaturated carboxylic acid copolymer, or a self-crosslinking agent, may be included. These crosslinking agents are preferably soluble in the solvent used.
[0060] Examples of crosslinking agents include melamine-based, substituted urea-based, or polymer-based crosslinking agents, which can be used individually or in combination. Furthermore, crosslinking agents having at least two crosslinking-forming substituents are preferred. Examples include compounds such as CYMEL (registered trademark), methoxymethylated glycourea, butoxymethylated glycourea, hydroxymethylated glycourea, methoxymethylated melamine, butoxymethylated melamine, hydroxymethylated melamine, methoxymethylated benzoguanamine, butoxymethylated benzoguanamine, hydroxymethylated benzoguanamine, methoxymethylated urea, butoxymethylated urea, hydroxymethylated urea, methoxymethylated thiourea, methoxymethylated thiourea, and hydroxymethylated thiourea, as well as condensates of these compounds.
[0061] The aforementioned crosslinking agent can undergo a crosslinking reaction with the surface functional groups of the graphene oxide, olefin-unsaturated carboxylic acid copolymers, or their salts. Additional crosslinking agents that react with the crosslinking agent can also be added. As additional crosslinking agents, there are no particular limitations on compounds having two or more functional groups that are reactive with oxazoline groups, such as carboxyl, hydroxyl, thiol, amino, sulfinic acid, or epoxy groups; compounds having two or more carboxyl groups are preferred. Furthermore, compounds having functional groups that generate the aforementioned functional groups and induce crosslinking reactions under heating during film formation or in the presence of an acid catalyst, such as sodium, potassium, lithium, or ammonium salts of carboxylic acids, can also be used as crosslinking agents.
[0062] As self-crosslinking crosslinking agents, examples include compounds that have crosslinking functional groups that react with each other within the same molecule (e.g., aldehyde, epoxy, vinyl, isocyanate, alkoxy groups relative to hydroxyl groups; aldehyde, amino, isocyanate, epoxy groups relative to carboxyl groups; isocyanate, aldehyde, etc. relative to amino groups); and compounds that have the same crosslinking functional groups that react with each other (hydroxyl groups (dehydration condensation), mercapto groups (disulfide bonds), ester groups (Claysen condensation), silanol groups (dehydration condensation), vinyl groups, acryloyl groups, etc.).
[0063] Specific examples of self-crosslinking crosslinking agents include polyfunctional acrylates, tetraalkoxysilanes, monomers having blocked isocyanate groups, and block copolymers having at least one monomer having hydroxyl, carboxylic acid, or amino groups, which exhibit crosslinking reactivity in the presence of an acid catalyst.
[0064] Such self-crosslinking crosslinking agents are also available as commercially available products. These commercially available products include, as polyfunctional acrylates, such as A-9300 (epoxylated glycerine triacrylate, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), A-GLY-9E (Ethoxylated glycerine triacrylate (EO9mol), manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), and A-TMMT (pentaerythritol tetraacrylate, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.); as tetraalkoxysilanes, such as tetramethoxysilane (manufactured by Tokyo Chemical Industry Co., Ltd.) and tetraepoxysilane (manufactured by Toyoko Chemical Co., Ltd.); and as polymers with blocked isocyanate groups, such as the ELASTRON series E-37, H-3, H38, BAP, NEW BAP-15, C-52, F-29, W-11P, MF-9, and MF-25K (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.).
[0065] When a crosslinking agent is included, its content varies depending on the solvent used, the substrate used, the required viscosity, the required film shape, etc., and is preferably 0.001 to 1000 parts by mass relative to 100 parts by mass of the olefin-unsaturated carboxylic acid copolymer or its salt, more preferably 0.001 to 100 parts by mass, and even more preferably 0.001 to 50 parts by mass. These crosslinking agents can also sometimes induce crosslinking reactions caused by self-condensation, and can induce crosslinking reactions with the dispersant. When crosslinking substituents are present in the dispersant, these crosslinking substituents are used to promote the crosslinking reaction.
[0066] [Matrix Polymer]
[0067] In the compositions of the present invention, a polymer that serves as the matrix may be added. Examples of matrix polymers include fluorinated resins such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer [P(VDF-HFP)], and vinylidene fluoride-chlorotrifluoroethylene copolymer [P(VDF-CTFE)]; polyolefin resins such as polyvinylpyrrolidone, ethylene-propylene-diene terpolymer, PE (polyethylene), PP (polypropylene), EVA (ethylene-vinyl acetate copolymer), and EEA (ethylene-ethyl acrylate copolymer); polystyrene resins such as polystyrene, HIPS (high-impact polystyrene), AS (acrylonitrile-styrene copolymer), ABS (acrylonitrile-butadiene-styrene copolymer), MS (methyl methacrylate-styrene copolymer), and styrene-butadiene rubber; polycarbonate resins; vinyl chloride resins; polyamide resins; polyimide resins; sodium polyacrylate; and PMMA. (Meth)acrylic resins such as polymethyl methacrylate; polyester resins such as PET (polyethylene terephthalate), polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, PLA (polylactic acid), poly-3-hydroxybutyric acid, polycaprolactone, polybutylene succinate, and polyethylene glycol succinate / adipate; polyphenylene ether resins; modified polyphenylene ether resins; polyacetal resins; polysulfone resins; polyphenylene sulfide resins; and polyethylene glycol succinate / adipate. Enol resins; polyglycolic acid; modified starch; cellulose acetate, carboxymethyl cellulose, cellulose triacetate; chitin, chitosan; thermoplastic resins such as lignin, polyaniline and aniline green group as its semi-oxide; polythiophene; polypyrrole; polyphenylene vinylidene; polyphenylene; polyacetylene and other conductive polymers, and further epoxy resins; urethane acrylates; phenolic resins; melamine resins; urea-formaldehyde resins; alkyd resins and other thermosetting resins, photocurable resins, etc. In the conductive carbon material dispersion of the present invention, water is preferably used as a solvent, and therefore, water-soluble matrix polymers are also preferred as matrix polymers. Examples of water-soluble matrix polymers include sodium polyacrylate, sodium carboxymethyl cellulose, water-soluble cellulose ethers, sodium alginate, polyvinyl alcohol, polystyrene sulfonic acid, polyethylene glycol, etc., with sodium polyacrylate and sodium carboxymethyl cellulose being particularly preferred.
[0068] The matrix polymer can also be obtained as a commercially available product. Examples of such commercially available products include sodium polyacrylate (manufactured by Fujifilm and Kohden Chemical Co., Ltd., degree of polymerization 2700-7500), sodium carboxymethyl cellulose (manufactured by Fujifilm and Kohden Chemical Co., Ltd.), sodium alginate (manufactured by Kanto Chemical Co., Ltd., grade 1), METOLOSE SH series (hydroxypropyl methylcellulose, manufactured by Shin-Etsu Chemical Industry Co., Ltd.), METOLOSE SE series (hydroxyethyl methylcellulose, manufactured by Shin-Etsu Chemical Industry Co., Ltd.), JC-25 (fully saponified polyvinyl alcohol, manufactured by VAM & Poval Co., Ltd.), JM-17 (intermediate saponified polyvinyl alcohol, manufactured by VAM & Poval Co., Ltd.), JP-03 (partially saponified polyvinyl alcohol, manufactured by VAM & Poval Co., Ltd.), and polystyrene sulfonic acid (manufactured by Aldrich, 18% by mass, aqueous solution).
[0069] When using a base polymer, its content is not particularly limited, but is preferably 0.001 to 1000 parts by mass relative to 100 parts by mass of the olefin-unsaturated carboxylic acid copolymer or its salt, more preferably 0.001 to 900 parts by mass.
[0070] [Preparation method of the composition]
[0071] The preparation method of the composition of the present invention is not particularly limited. A dispersion can be prepared by mixing graphene oxide or its salt, olefin-unsaturated carboxylic acid copolymer or its salt, solvent, and other components as needed, in any order. Furthermore, from the viewpoint of highly dispersing graphene oxide or its salt to obtain a uniform dispersion, dispersion treatment of the mixture is preferred. Examples of dispersion treatments include wet treatment using ball mills, bead mills, jet mills, etc., and ultrasonic treatment using a bath-type or probe-type ultrasonic crusher. Wet treatment using a jet mill and ultrasonic treatment are particularly preferred.
[0072] The dispersion treatment time is arbitrary, preferably from 1 minute to about 10 hours, and more preferably from 5 minutes to about 5 hours. During this time, stirring, cooling, or heating treatments can be carried out as needed.
[0073] Furthermore, when using any components such as a matrix polymer, these can be added after preparing a uniform dispersion containing graphene oxide or its salt, an olefin-unsaturated carboxylic acid copolymer or its salt, a solvent, and a crosslinking agent as needed.
[0074] In this invention, there is no particular limitation on the concentration of the solid components in the composition. However, considering the formation of an artificial SEI layer by weight per unit area and in terms of film thickness, a concentration of 10% by mass or less is preferred, more preferably 5% by mass or less, and even more preferably 3% by mass or less. Furthermore, the lower limit is arbitrary; from a practical point of view, 0.01% by mass or more is preferred, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more.
[0075] Regarding the viscosity of the composition, considering the coatability to substrates such as current collector substrates, a viscosity of 0.1 to 20 mPa is preferred. s, more preferably 1-10 mPa s. Here, viscosity is the viscosity at 25°C as measured using an E-type viscometer.
[0076] [Artificial solid electrolyte interface layer and negative electrode for secondary batteries]
[0077] The thin film (artificial solid electrolyte interface layer) obtained by coating the composition described above onto one side of a substrate (e.g., a negative electrode current collector substrate, a lithium metal deposition promotion layer formed on the negative electrode current collector substrate, etc.) and drying it naturally or by heating can be suitable as an artificial SEI layer for a negative electrode of a secondary battery.
[0078] As the negative electrode current collector substrate, a current collector substrate conventionally used as an electrode substrate in energy storage devices can be used. For example, materials such as copper, aluminum, titanium, stainless steel, nickel, gold, silver and alloys thereof, carbon materials, metal oxides, and conductive polymers can be used. Metal foil (metal substrate) made of copper, aluminum, nickel, or alloys thereof is preferred, and copper foil is more preferred. Furthermore, when used as the negative electrode current collector substrate for a lithium secondary battery, a negative electrode current collector substrate that does not react with lithium metal is preferred.
[0079] There is no particular limitation on the thickness of the current collector substrate, but in this invention, 1 to 100 μm is preferred.
[0080] Examples of coating methods for the composition include spin coating, dip coating, flow coating, inkjet coating, casting coating, doctor blade coating, bar coating, photogravure coating, slot coating, roller coating, flexographic printing, transfer printing, brush coating, doctor blade coating, air knife coating, and embossing coating. From the perspective of operational efficiency, inkjet coating, casting coating, dip coating, bar coating, doctor blade coating, roller coating, photogravure coating, flexographic printing, spray coating, and embossing coating are preferred. The temperature during heating and drying is arbitrary, preferably around 30–200°C, more preferably around 50–150°C. The drying time is not particularly limited as long as the solvent can be evaporated; typically, 5–20 minutes is preferred.
[0081] Regarding the thickness of the SEI layer, considering the reduction in internal resistance and film thickness uniformity of the resulting device, it is preferably 1 μm or less, more preferably 500 nm or less, even more preferably 200 nm or less, and even more preferably 100 nm or less. Furthermore, there is no particular limitation on the lower limit; considering the film strength, it is preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more. The film thickness of the artificial SEI layer can be determined, for example, by cutting a test piece of appropriate size from the current collector substrate on which the artificial SEI layer has been formed, exposing the cross-section using a focused ion beam method or the like, and observing it under a microscope such as a scanning electron microscope (SEM) from the portion of the undercoating layer exposed in the cross-section.
[0082] The negative electrode for secondary batteries can be constructed by forming a negative electrode active material layer as needed in the aforementioned negative electrode current collector having an artificial SEI layer. The negative electrode for secondary batteries of the present invention can be used as a negative electrode for various secondary batteries, such as electric double-layer capacitors, lithium secondary batteries, lithium-ion secondary batteries, proton polymer batteries, nickel-metal hydride batteries, aluminum solid capacitors, electrolytic capacitors, lead-acid batteries, etc. The negative electrode for secondary batteries of the present invention is preferably used in lithium secondary batteries, especially anode-free lithium metal secondary batteries (anode-free batteries).
[0083] Furthermore, when the manufactured secondary battery is an anode-less battery, it does not have a negative electrode active material layer during manufacturing, so a negative electrode current collector with the aforementioned artificial SEI layer can be used directly. In this case, lithium ions moving from the positive electrode side during charging are deposited as lithium metal on the negative electrode current collector substrate, thereby forming a negative electrode active material layer.
[0084] Furthermore, in this invention, the phrase "lithium metal deposited on the negative electrode current collector substrate" means, unless otherwise specified, that lithium metal is deposited on at least a portion of the surface of the negative electrode current collector substrate and the surface of the artificial SEI layer formed on the surface of the negative electrode current collector substrate. Therefore, in a lithium secondary battery, lithium metal can, for example, be deposited on the surface of the negative electrode current collector substrate (at the interface between the negative electrode current collector substrate and the artificial SEI layer).
[0085] The negative electrode active material layer can be formed by coating a negative electrode slurry (a composition for forming the negative electrode active material layer) made of negative electrode active material, binder polymer, and solvent as needed onto a substrate, and then drying it naturally or by heating. Alternatively, the negative electrode active material layer can also be formed by molding a mixture of negative electrode active material and binder polymer into a sheet (dry method).
[0086] As a negative electrode active material, it can use materials selected from alkali metals, alkali alloys, and adsorption materials. The element that emits lithium ions is an elemental substance, oxide, sulfide, nitride, or reversibly resorbable element from at least one of the elements in groups 4 to 15 of the periodic table. Carbon materials that release lithium ions.
[0087] Examples of alkali metals include Li, Na, and K. Examples of alkali metal alloys include Li-Al, Li-Mg, Li-Al-Ni, Na-Hg, and Na-Zn.
[0088] Examples of simple substances of an element selected from at least one of the elements in groups 4 to 15 of the periodic table that absorb, retain, or release lithium ions include silicon, tin, aluminum, zinc, and arsenic.
[0089] Also listed as oxides are silicon monoxide (SiO), silicon dioxide (SiO2), tin silicon oxide (SnSiO3), lithium bismuth oxide (Li3BiO4), lithium zinc oxide (Li2ZnO2), and lithium titanate (LTO, Li4Ti5O). 12 ), titanium dioxide, etc.
[0090] Also an example of a sulfide is lithium iron sulfide (Li). x FeS2 (0≤x≤3) and lithium copper sulfide (Li x CuS (0≤x≤3) etc.
[0091] Also as nitrides, examples include lithium-containing transition metal nitrides, specifically, Li... x M y N (M = Co, Ni, Cu, 0≤x≤3, 0≤y≤0.5), lithium iron nitride (Li3FeN4), etc.
[0092] As a reversible adsorption Carbon materials that release lithium ions include graphite, carbon black, coke, glassy carbon, carbon fiber, carbon nanotubes, or sintered forms of these.
[0093] As the binder polymer, it is possible to appropriately select from known materials, such as polyvinylidene fluoride (PVdF), polyvinylpyrrolidone, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer [P(VDF-HFP)], vinylidene fluoride-chlorotrifluoroethylene copolymer [P(VDF-CTFE)], polyvinyl alcohol, polyimide, ethylene-propylene-diene terpolymer, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyaniline, polyimide, and polyamide. Furthermore, the content of the binder polymer relative to 100 parts by weight of the negative electrode active material is preferably 0.1 to 40 parts by weight, and particularly preferably 1 to 30 parts by weight.
[0094] As solvents, examples of solvents used in the above compositions can be listed, and appropriate selection can be made from these depending on the type of adhesive. In the case of non-water-soluble adhesives such as PVdF, NMP is preferred, and in the case of water-soluble adhesives such as SBR-CMC and PAA, water is preferred. In the case of manufacturing dry electrodes, solvents may not be required.
[0095] Furthermore, the aforementioned negative electrode slurry may contain conductive materials. Examples of conductive materials include carbon black, Ketjen black, acetylene black, carbon whiskers, carbon fibers, natural graphite, artificial graphite, titanium oxide, ruthenium oxide, aluminum, nickel, etc., with graphite (both natural and artificial graphite) being preferred.
[0096] When forming a negative electrode active material layer on an artificial SEI layer, methods for forming this negative electrode active material layer include pressing a negative electrode composition prepared without solvent onto a substrate (dry method), and preparing a negative electrode slurry using a solvent, coating it onto the substrate, and drying it (wet method). There are no particular limitations on these methods, and various conventionally known methods can be used. For example, examples of wet methods include various printing methods such as offset printing and screen printing, blade coating, dip coating, spin coating, rod coating, slot coating, inkjet coating, and embossing coating.
[0097] Furthermore, in the case of heat drying, either natural drying or heat drying can be used; from the viewpoint of manufacturing efficiency, heat drying is preferred. When heat drying is carried out, the temperature is preferably around 50 to 400°C, and more preferably around 70 to 150°C.
[0098] There is no particular limitation on the thickness of the aforementioned negative electrode active material layer (thin film), but it is preferably about 0.01 to 1000 μm, more preferably about 5 to 300 μm. Furthermore, when the thin film is fabricated as an electrode separately, it is preferable to have a film thickness of 10 μm or more.
[0099] The thickness of the negative electrode active material layer can be determined using known methods such as micrometer measurement. For example, it can be determined by measuring the overall thickness of the fabricated negative electrode and subtracting the thickness of the current collector substrate and the artificial SEI layer from it.
[0100] The negative electrode for the aforementioned secondary battery can be pressed as needed. The pressing method can be any commonly used method, with molding and rolling being particularly preferred. Furthermore, there is no particular limitation on the pressing pressure, but 1 kN / cm or higher is preferred, 2 kN / cm or higher is more preferred, and 5 kN / cm or higher is even more preferred. Additionally, there is no particular limitation on the upper limit of the above pressing pressure, but 50 kN / cm or lower is preferred.
[0101] [Rechargeable Battery]
[0102] The secondary battery involved in this invention includes the negative electrode for a secondary battery as described above, and more specifically, is composed of at least one pair of positive and negative electrodes, a separator between these electrodes, and an electrolyte. Examples of such secondary batteries include lithium secondary batteries, lithium-ion secondary batteries, lithium-air secondary batteries, lithium-ion capacitors, sodium secondary batteries, sodium-ion batteries, sodium-ion capacitors, potassium secondary batteries, potassium-ion secondary batteries, zinc secondary batteries, zinc-ion secondary batteries, nickel-zinc secondary batteries, manganese-zinc secondary batteries, zinc-air secondary batteries, manganese secondary batteries, manganese-ion batteries, manganese-air batteries, aluminum metal secondary batteries, aluminum-ion secondary batteries, aluminum-air secondary batteries, lead-acid batteries, etc., with lithium secondary batteries being preferred, and anode-free lithium metal secondary batteries (anode-free batteries) being more preferred.
[0103] The secondary battery of the present invention is characterized in that, using the above-mentioned secondary battery with a negative electrode as the negative electrode, the positive electrode, separator, electrolyte, etc., which are other constituent components, can be appropriately selected from known materials.
[0104] The positive electrode consists of a positive current collector substrate and a layer of positive active material formed on the current collector substrate.
[0105] As the positive electrode current collector substrate, a current collector substrate conventionally used as an electrode substrate for energy storage devices can be used. For example, materials such as copper, aluminum, titanium, stainless steel, nickel, gold, silver and alloys thereof, carbon materials, metal oxides, and conductive polymers can be used. Metal foil (metal substrate) made of copper, aluminum, nickel, or alloys thereof is preferred, and copper foil is more preferred. In this invention, the selection can be made by considering combinations with the aforementioned negative electrode current collector substrate.
[0106] There is no particular limitation on the thickness of the current collector substrate, but in this invention, 1 to 100 μm is preferred.
[0107] The positive electrode active material layer can be formed by coating a positive electrode slurry (a composition for forming the positive electrode active material layer) made of positive electrode active material, binder polymer, and solvent as needed onto a substrate, followed by natural or heat drying. Alternatively, the positive electrode active material layer can also be formed by molding a mixture of positive electrode active material and binder polymer into a sheet (dry method).
[0108] As a positive electrode active material, various active materials previously used in electrodes of energy storage devices can be used. For example, in the case of lithium secondary batteries and lithium-ion secondary batteries, adsorbent materials can be used as the positive electrode active material. Chalcogenides that are free from lithium ions or chalcogenides containing lithium ions, polyanionic compounds, elemental sulfur and its compounds, etc.
[0109] Examples of chalcogenides that can adsorb and desorb such lithium ions include FeS2, TiS2, MoS2, V2O6, and V6O. 13 MnO2, etc.
[0110] Examples of chalcogenides containing lithium ions include LiCoO2, LiMnO2, LiMn2O4, LiMo2O4, LiV3O8, LiNiO2, and Li. x Ni y M 1-y O2 (where M represents at least one metallic element selected from Co, Mn, Ti, Cr, V, Al, Sn, Pb and Zn, with 0.05≤x≤1.10 and 0.5≤y≤1.0), etc.
[0111] Examples of polyanionic compounds include LiFePO4.
[0112] Examples of sulfur compounds include Li₂S and erythrine.
[0113] In addition, in the case of lithium-ion capacitors and sodium-ion capacitors, carbonaceous materials can be used as the active material.
[0114] Examples of carbonaceous materials include activated carbon with high specific surface area, such as activated carbon obtained by carbonizing synthetic resins such as phenolic resins and natural materials such as coconut shells and then performing activation treatment.
[0115] As the aforementioned binder polymer, the same binder polymer exemplified in the description of the negative electrode slurry can be cited. Furthermore, the content of the binder polymer relative to 100 parts by weight of the positive electrode active material is preferably 0.1 to 40 parts by weight, and particularly preferably 1 to 30 parts by weight.
[0116] As solvents, examples of solvents used in the above compositions can be listed. Among these, the solvent can be appropriately selected according to the type of adhesive. In the case of non-water-soluble adhesives such as PVdF, NMP is preferred, and in the case of water-soluble adhesives such as SBR-CMC and PAA, water is preferred. In the case of manufacturing dry electrodes, solvents may not be required.
[0117] Furthermore, the aforementioned positive electrode paste may contain a conductive material. Examples of conductive materials include those exemplified in the description of the negative electrode paste.
[0118] Methods for forming the positive electrode active material layer include pressing a positive electrode composition prepared without solvent onto a substrate (dry method); or preparing a positive electrode slurry using a solvent, coating it onto a substrate, and drying it (wet method). These methods are not particularly limited, and various conventionally known methods can be used. For example, wet methods include various printing methods such as offset printing and screen printing, blade coating, dip coating, spin coating, rod coating, slot coating, inkjet coating, and molding coating.
[0119] Furthermore, in the case of heat drying, either natural drying or heat drying can be used; from the viewpoint of manufacturing efficiency, heat drying is preferred. When heat drying is carried out, the temperature is preferably around 50 to 400°C, and more preferably around 70 to 150°C.
[0120] The thickness of the positive electrode active material layer is preferably 10–500 μm, and more preferably 30–100 μm, from the perspective of improving electrode capacity, increasing energy density and suppressing resistance.
[0121] The thickness of the positive electrode active material layer can be determined using known methods such as micrometer measurement. For example, it can be determined by measuring the overall thickness of the fabricated positive electrode and subtracting the thickness of the positive electrode current collector substrate from it.
[0122] The positive electrode for the aforementioned secondary battery can be pressed as needed. The pressing method can be any commonly used method, with molding and rolling being particularly preferred. Furthermore, there is no particular limitation on the pressing pressure, but 1 kN / cm or more is preferred, 2 kN / cm or more is more preferred, and 5 kN / cm or more is more preferred. Additionally, there is no particular limitation on the upper limit of the above pressing pressure, but 50 kN / cm or less is preferred.
[0123] Examples of membranes include cellulose-based membranes, polyolefin-based membranes, and glass fiber-based membranes.
[0124] As an electrolyte, liquid electrolytes or solid electrolytes formed by dissolving electrolyte salts in a solvent are both acceptable. In addition, both aqueous and non-aqueous electrolytes are acceptable. The electrodes of the energy storage device of the present invention are preferably suitable for batteries that use solid electrolytes, especially all-solid-state batteries (e.g., all-solid-state lithium-ion batteries).
[0125] Examples of electrolyte salts include lithium salts such as LiPF6, iBF4, LiN(SO2F)2, LiN(C2F5SO2)2, LiAsF6, LiSbF6, LiAlF4, LiGaF4, LiInF4, LiClO4, LiN(CF3SO2)2, LiCF3SO3, LiSiF6, LiN(CF3SO2), and (C4F9SO2); metal iodides such as LiI, NaI, KI, CsI, and CaI2; iodide salts of quaternazonium compounds; iodide salts and perchlorates of tetraalkylammonium compounds; and metal bromides such as LiBr, NaBr, KBr, CsBr, and CaBr2. These electrolyte salts can be used individually or in combination of two or more.
[0126] As a solvent for the electrolyte, there are no particular limitations as long as it does not corrode or decompose the materials constituting the battery, thus degrading their performance, or dissolving the aforementioned electrolyte salts. For example, as a non-aqueous solvent, cyclic esters such as ethylene carbonate (EC), propylene carbonate, butyl carbonate, and γ-butyrolactone; ethers such as tetrahydrofuran and dimethoxyethane; chain esters such as methyl acetate, dimethyl carbonate, diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); and nitriles such as acetonitrile can be used. One of these solvents can be used alone, or two or more can be used in combination.
[0127] To enhance the function of the artificial solid electrolyte interface, additives can be included in the electrolyte to promote the formation of the natural SEI layer. Examples of such additives include vinylene carbonate (VC), 1-propylene 1,3-sulfonolactone (PS), fluoroethylene carbonate (FEC), and 4-(trifluoromethyl)-1,3-dioxolane-2-one.
[0128] As solid electrolytes, inorganic solid electrolytes such as sulfide-based solid electrolytes and oxide-based solid electrolytes, as well as organic solid electrolytes such as polymer-based solid electrolytes, are preferred. By using these solid electrolytes, it is possible to obtain an all-solid-state battery that does not use an electrolyte.
[0129] As sulfide-based solid electrolytes, examples include lithium sulfide silicon-based materials such as Li2S-SiS2-lithium compounds (where the lithium compound is selected from at least one of Li3PO4, LiI and Li4SiO4), Li2S-P2S5, Li2S-P2O5, Li2S-B2S5, and Li2S-P2S5-GeS2.
[0130] As an oxide-based solid electrolyte, Li5La3M2O, which is an oxide with a garnet-type structure, can be listed as an example. 12 (M=Nb, Ta), Li7La3Zr2O 12The compounds collectively known as LISICON are oxoacid salts with a γ-Li3PO4 structure as their basic component; perovskite-type compounds are collectively known as LIPON. 3.3 PO 3.8 N 0.22 Sodium / aluminum oxide, etc.
[0131] As a polymeric solid electrolyte, examples include polyethylene oxide materials and polymers obtained by polymerizing or copolymerizing elements such as hexafluoropropylene, tetrafluoroethylene, trifluoroethylene, ethylene, propylene, acrylonitrile, vinylidene chloride, acrylic acid, methacrylic acid, methyl acrylate, ethyl acrylate, methyl methacrylate, styrene, and vinylidene fluoride.
[0132] Furthermore, polymeric solid electrolytes may contain supporting salts and plasticizers.
[0133] Specific examples of supporting salts include lithium (fluorosulfonylimide), and examples of plasticizers include succinate.
[0134] Example
[0135] The following examples and comparative examples illustrate the present invention in more detail, but the present invention is not limited to the following examples.
[0136] The apparatus used in the embodiments is described below.
[0137] Probe-type ultrasonic irradiation device
[0138] Hielscher Ultrasonics, UIP1000hd
[0139] In addition, the raw materials used are as follows.
[0140] Graphene oxide: manufactured by EMD Millipore (now Merck)
[0141] ZAIKTHENE L: ZAIKTHENE L (manufactured by Sumitomo Seika Co., Ltd., 24.5% by mass solids concentration of poly(ethylene-acrylic acid) 2-hydroxyethyl dimethylamine brine dispersion, Cole counter method, particle size less than 0.1 μm)
[0142] WS-300: WS-300 (manufactured by Nippon Shokubai Co., Ltd.), an aqueous solution containing an oxazoline polymer, EPOCROS (registered trademark) WS-300, weight-average molecular weight: 1.2 × 10⁻⁶. 5 Solid content concentration: 10.0% by mass
[0143] CHEMIPEARL S100: CHEMIPEARL S100 (Mitsui Chemicals, 27% by mass solids concentration, poly(ethylene-methacrylic acid) partially sodium brine dispersion, Cole counter method, particle size less than 0.1 μm)
[0144] (1) Preparation of compositions for forming artificial solid electrolyte interface layers
[0145] [Example 1-1]
[0146] In a 100mL polypropylene bottle, 7.00g of graphene oxide aqueous dispersion paste (Merck, 1.0% by mass, 0.070g solids), 60.82g of pure water, 1.89g of lithium hydroxide aqueous solution (1.00% by mass, 0.0189g solids), and 0.286g of ZAIKTHENE L (Sumitomo Seika Co., Ltd., 24.5% by mass poly(ethylene-acrylic acid) 2-hydroxyethyl dimethylamine saline dispersion, Cole counter method particle size less than 0.1μm) (0.070g solids) were added sequentially (0.070g solids) and stirred to obtain a black mixture. This black mixture was then stirred with a magnetic stirrer under ice-cold conditions and irradiated with ultrasound at 500W for 3 minutes using a UIP1000hd probe-type ultrasonic irradiation device (Hielsher). After irradiation, the container was removed, and the liquid was agitated to homogenize it. The ultrasonic treatment was repeated three times to obtain a black uniform dispersion A-1 (solid component concentration 0.2% by mass).
[0147] It should be noted that the amount of lithium hydroxide aqueous solution added is the sum of the graphene neutralization amount of 20 phr (relative to the solid content of graphene oxide, 20% by mass of lithium hydroxide) calculated beforehand by neutralizing and titrating the graphene oxide, and the ZAIKTHENE L neutralization amount of 7.0 phr (relative to the solid content of ZAIKTHENE L, 7.0% by mass of lithium hydroxide), which is 1 equivalent of the carboxyl groups contained in ZAIKTHENE L. Unless otherwise specified, the amount of lithium hydroxide aqueous solution added in the following examples and comparative examples is also calculated using the same method.
[0148] [Examples 1-2]
[0149] Except for changing the amount of graphene oxide aqueous dispersion paste to 35.00 g (0.35 g solids), the amount of pure water to 24.12 g, the amount of lithium hydroxide aqueous solution to 9.45 g (0.0945 g solids), and the amount of ZAIKTHENE L to 1.43 g (0.35 g solids), a black uniform dispersion A-2 (1.0% by mass) was obtained using the same method as in Examples 1-1.
[0150] [Comparative Example 1-1]
[0151] In a 100mL polypropylene bottle, 0.245g of ZAIKTHENE L (0.060g solids), 23.35g of pure water, 0.420g of lithium hydroxide aqueous solution (0.0042g solids), and 5.99g of 2-propanol were added sequentially and stirred to obtain a colorless and transparent solution B-1 (0.2% by mass of solids). Furthermore, 2-propanol was added to improve the uniformity of the coating surface of the artificial solid electrolyte interface layer in Example 2 described later.
[0152] [Comparative Examples 1-2]
[0153] The amount of ZAIKTHENE L used was changed to 1.22 g (0.30 g solid component), and 20.69 g of pure water, 2.10 g of lithium hydroxide aqueous solution (0.021 g solid component), and 5.99 g of 2-propanol were added sequentially. After stirring, a colorless and transparent solution B-2 (solid component concentration 1.0% by mass) was obtained. Furthermore, 2-propanol was added to improve the uniformity of the coating surface of the artificial solid electrolyte interface layer in Example 2.
[0154] [Comparative Examples 1-3]
[0155] Except that EPOCROS WS-300 0.700 g (0.070 g solids) was used instead of ZAIKTHENE L and an aqueous lithium hydroxide solution was not used, a black uniform dispersion B-3 (0.2% by mass of solids) was obtained using the same method as in Examples 1-1.
[0156] [Comparative Examples 1-4]
[0157] Except that EPOCROS WS-300 3.50 g (0.35 g solids) was used instead of ZAIKTHENE L and an aqueous lithium hydroxide solution was not used, a black uniform dispersion B-4 (1.0 wt% solids concentration) was obtained using the same method as in Examples 1-2.
[0158] [Comparative Examples 1-5]
[0159] Except for replacing ZAIKTHENE L with CHEMIPEARL S-100 0.259 g (0.070 g solids) and changing the amount of lithium hydroxide aqueous solution used to 1.40 g (0.014 g solids), a black uniform dispersion B-5 (0.2% by mass solids concentration) was obtained using the same method as in Examples 1-1. Furthermore, the amount of lithium hydroxide added was considered only as a graphene oxide neutralization amount of 20 phr (20% by mass relative to the graphene oxide solids content).
[0160] [Comparative Examples 1-6]
[0161] Except for replacing ZAIKTHENE L with CHEMIPEARL S-100 (Mitsui Chemicals Co., Ltd., 27% by mass poly(ethylene-methacrylic acid) partial sodium salt dispersion, Cole counter method particle size less than 0.1 μm) 1.30 g (0.35 g solids), and changing the amount of lithium hydroxide aqueous solution to 7.00 g (0.070 g solids), a black uniform dispersion B-6 (1.0% by mass solids) was obtained using the same method as in Examples 1-2.
[0162] It should be noted that the amount of lithium hydroxide added is only considered as 20 phr of graphene oxide neutralization (20% by mass relative to the solid content of graphene oxide).
[0163] (2) Formation of artificial solid electrolyte interface layer
[0164] [Example 2-1]
[0165] Dispersion A-1 was spread on copper foil (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., electrolytic copper foil, 15 μm thick) using a wire-wound bar coater (OSP-6, maximum wet film thickness 6 μm, coating speed 3 m / min). Then, it was dried in an oven at 120°C for 10 minutes to form an artificial solid electrolyte interface layer, resulting in copper foil C-1 with this interface layer. The coating surface of C-1 was visually observed to be uniform. The film thickness of the artificial solid electrolyte interface layer, based on SEM observations, is estimated to be an average of 12 nm.
[0166] [Example 2-2]
[0167] Except for changing dispersion A-1 to A-2, copper foil C-2 with an artificial solid electrolyte interface layer was obtained using the same method as in Example 2-1. The coating surface of C-2 appeared uniform upon visual observation. The film thickness of the artificial solid electrolyte interface layer was estimated to be 60 nm based on SEM observations.
[0168] [Comparative Example 2-1]
[0169] Except for changing dispersion A-1 to B-1, copper foil D-1 with an artificial solid electrolyte interface layer was obtained using the same method as in Example 2-1. The coating surface of D-1 appeared uniform upon visual inspection. The film thickness of the artificial solid electrolyte interface layer, based on SEM observations, is estimated to be an average of 12 nm.
[0170] [Comparative Example 2-2]
[0171] Except for changing dispersion A-1 to B-2, copper foil D-2 with an artificial solid electrolyte interface layer was obtained using the same method as in Example 2-1. Visual inspection revealed significant unevenness in the coating surface of D-2, making it unsuitable as an artificial solid electrolyte interface layer requiring a defect-free, uniform coating surface.
[0172] [Comparative Examples 2-3]
[0173] Except for changing dispersion A-1 to B-3, copper foil D-3 with an artificial solid electrolyte interface layer was obtained using the same method as in Example 2-1. The coating surface of D-3 appeared uniform upon visual inspection. The film thickness of the artificial solid electrolyte interface layer, based on SEM observations, is estimated to be an average of 12 nm.
[0174] [Comparative Examples 2-4]
[0175] Except for changing dispersion A-1 to B-4, copper foil D-4 with an artificial solid electrolyte interface layer was obtained using the same method as in Example 2-1. The coating surface of D-4 appeared uniform upon visual inspection. The film thickness of the artificial solid electrolyte interface layer, based on SEM observations, is estimated to be an average of 60 nm.
[0176] [Comparative Examples 2-5]
[0177] Except for changing dispersion A-1 to B-5, copper foil D-5 with an artificial solid electrolyte interface layer was obtained using the same method as in Example 2-1. The coating surface of D-5 appeared uniform upon visual inspection. The film thickness of the artificial solid electrolyte interface layer, based on SEM observations, is estimated to be an average of 12 nm.
[0178] [Comparative Examples 2-6]
[0179] Except for changing dispersion A-1 to B-6, copper foil D-6 with an artificial solid electrolyte interface layer was obtained using the same method as in Example 2-1. The coating surface of D-6 appeared uniform upon visual inspection. The film thickness of the artificial solid electrolyte interface layer, based on SEM observations, is estimated to be an average of 60 nm.
[0180] For the copper foils with artificial solid electrolyte interface layers prepared in Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-6, the coating uniformity and scratch resistance of the coating surface were evaluated using the following methods.
[0181] <Coating area and coating uniformity>
[0182] The coatings (black dispersion) of the artificial solid electrolyte interface layer formation composition applied to metal foil using a wire-wound bar coater were visually evaluated immediately after spreading and after drying. Coating uniformity was evaluated based on the condition of the dried coating surface using the following criteria. The evaluation results are shown in Table 1.
[0183] Evaluation Criteria for Coating Uniformity
[0184] A: By visual inspection, more than half of the coating surface is uniform.
[0185] B: Visually inspected, the coating surface exhibits an uneven surface with a uniform pattern.
[0186] (C: Visually, the entire surface of the coating is noticeably uneven.)
[0187] The case in which an evaluation of "A" was obtained in the above coating uniformity test is set as qualified.
[0188] <Abrasion resistance (dry Bemcot peel test)>
[0189] The contact area with the artificial solid electrolyte interface layer is 1 cm². 2 Non-woven cloth (manufactured by Asahi Kasei Corporation, Bemcot M-1) with 2kg / cm applied on one side 2 The load was applied to the metal foil surface and moved horizontally once. The condition of the artificial solid electrolyte interface layer at the wiped-off portion was visually confirmed, and evaluated using the following criteria. The results are shown in Table 1.
[0190] Evaluation Criteria
[0191] A: No damage was generated at the artificial solid electrolyte interface layer.
[0192] B: Linear scratches were found at the interface layer of the artificial solid electrolyte, confirming the exposure of the metal foil surface.
[0193] (C: The planar peeling at the artificial solid electrolyte interface layer confirmed the exposure of the metal foil surface.)
[0194] In the above scratch resistance test, the case in which an evaluation of "A" is obtained is considered qualified.
[0195] <Water Resistance (Aqueous Bemcot Peel Test)>
[0196] The contact area with the artificial solid electrolyte interface layer is 1 cm². 2 A non-woven fabric cloth (manufactured by Asahi Kasei Corporation, Bemcot M-1) moistened with water is applied at a rate of 2 kg / cm². 2 The load was applied to the metal foil surface and moved horizontally once. The condition of the artificial solid electrolyte interface layer at the wiped-off portion was visually confirmed, and evaluated using the following criteria. The results are shown in Table 1.
[0197] Evaluation Criteria
[0198] A: No damage was generated at the artificial solid electrolyte interface layer.
[0199] B: Linear scratches were found at the interface layer of the artificial solid electrolyte, confirming the exposure of the metal foil surface.
[0200] (C: The planar peeling at the artificial solid electrolyte interface layer confirmed the exposure of the metal foil surface.)
[0201] In the above water resistance test, a rating of "A" is considered acceptable.
[0202] [Table 1]
[0203]
[0204] The results in Table 1 confirm that the artificial solid electrolyte interface layer of the embodiments exhibits excellent coating uniformity, scratch resistance, and water resistance. Since the electrolytes used in secondary batteries generally contain electrolyte salts and are highly polar, it is assumed that the artificial solid electrolyte interface layer, with its excellent water resistance, also possesses excellent electrolyte resistance.
[0205] (3) Fabrication of anode-free lithium metal secondary batteries
[0206] [Example 3-1]
[0207] The copper foil C-1 with the artificial solid electrolyte interface layer prepared in Example 2-1 was punched to a diameter of 13 mm and dried at 120°C under vacuum for 3 hours to form an anode-less negative electrode. Separately, NCM523 (LiNi) fabricated on aluminum foil was... 0.5 Co 0.2 Mn 0.3 O2) / polyvinylidene fluoride (PVdF) / acetylene black (mass ratio 96:2:2, unit area weight 25mg / cm²) 2 The cathode material (90 μm thick) was punched to a diameter of 10 mm and dried at 120 °C under vacuum for 3 hours.
[0208] In addition to the negative and positive electrodes, a CR2032 coin cell was fabricated using two single-layer polypropylene membranes (Celgard Corporation, #2400) punched to a diameter of 15 mm as the separator and 1M LiPF4 / EC-DEC (1:1) as the electrolyte, following standard methods. For the electrolyte, 5 μL was added for each membrane layer, for a total of 10 μL. The fabricated coin cell was charged and discharged under the following conditions. The results are shown in Table 2.
[0209] Current: 0.307mA (0.391mA / cm for electrodes with a diameter of 10mm) 2 )
[0210] Voltage: Initial charge 0V~4.2V, initial discharge 4.2V~3.0V, subsequent charge / discharge 3.0V~4.2V
[0211] Charge / discharge cycles: 5 times
[0212] [Example 3-2-1]
[0213] Except for using C-2 instead of copper foil C-1 with an artificial solid electrolyte interface layer, which resulted in 10 charge-discharge cycles, the coin battery was fabricated and tested using the same method as in Example 3-1. The results are shown in Table 2.
[0214] [Example 3-2-2]
[0215] Except for using 1M LiPF4 / EC-EMC (3:7) as the electrolyte, the coin cell was fabricated and charge / discharge tested using the same method as in Example 3-2-1. The results are shown in Table 2.
[0216] [Example 3-2-3]
[0217] Except for the use of 1M LiPF4 / EC-EMC (3:7) as the electrolyte, and a mixture of VC 2% by mass and PS 0.5% by mass as an additive, the coin battery was fabricated and charge-discharge tested using the same method as in Example 3-2-1. The results are shown in Table 2.
[0218] [Comparative Example 3-1]
[0219] Except for using plain copper foil without a dispersion coating instead of copper foil C-1 with an artificial solid electrolyte interface layer, the coin battery was fabricated and charge / discharge tested using the same method as in Example 3-1. The results are shown in Table 2.
[0220] [Comparative Example 3-2]
[0221] Except for using D-1 instead of copper foil C-1 with an artificial solid electrolyte interface layer, the coin battery was fabricated and charge / discharge tested using the same method as in Example 3-1. The results are shown in Table 2.
[0222] [Comparative Example 3-3]
[0223] Except for using D-3 instead of copper foil C-1 with an artificial solid electrolyte interface layer, the coin battery was fabricated and charge / discharge tested using the same method as in Example 3-1. The results are shown in Table 2.
[0224] [Comparative Examples 3-4]
[0225] Except for using D-4 instead of copper foil C-1 with an artificial solid electrolyte interface layer, the coin battery was fabricated and charge / discharge tested using the same method as in Example 3-1. The results are shown in Table 2.
[0226] [Comparative Examples 3-5]
[0227] Except for using D-5 instead of copper foil C-1 with an artificial solid electrolyte interface layer, the coin battery was fabricated and charge / discharge tested using the same method as in Example 3-1. The results are shown in Table 2.
[0228] [Comparative Examples 3-6]
[0229] Except for using D-6 instead of copper foil C-1 with an artificial solid electrolyte interface layer, the coin battery was fabricated and charge / discharge tested using the same method as in Example 3-1. The results are shown in Table 2.
[0230] [Table 2]
[0231]
[0232] CE: Coulomb efficiency
[0233] Using the method described in the examples and employing copper foil with an artificial solid electrolyte interface layer, the obtained anode-free lithium metal secondary battery was found to have excellent coulombic efficiency, discharge capacity, and discharge capacity retention in charge-discharge tests.
Claims
1. A composition for forming an artificial solid electrolyte interface layer, comprising: graphene oxide or a salt thereof, an olefin-unsaturated carboxylic acid copolymer or a salt thereof, and a solvent containing water.
2. The artificial solid electrolyte interface layer-forming composition according to claim 1, wherein The salt of the graphene oxide is a lithium salt.
3. The artificial solid-electrolyte interphase layer-forming composition according to claim 1, wherein The salt of the olefin-unsaturated carboxylic acid copolymer is an amine salt, ammonium salt, or lithium salt of the ethylene-(meth)acrylic acid copolymer.
4. The artificial solid-electrolyte interphase layer-forming composition according to claim 1, wherein The graphene oxide contains carboxyl or phenolic hydroxyl groups as surface functional groups, and the oxygen element ratio is 20-60 atm.
5. The artificial solid-electrolyte interphase layer-forming composition according to claim 1, wherein The graphene oxide is a single-layer graphene oxide or a multilayer graphene oxide with a thickness of less than 5 nm.
6. An artificial solid electrolyte interface layer obtained from the composition for forming an artificial solid electrolyte interface layer according to any one of claims 1 to 5.
7. The artificial solid electrolyte interface layer according to claim 6, wherein the thickness is less than 1 μm.
8. A negative electrode for a secondary battery, wherein the artificial solid electrolyte interface layer as described in claim 6 is provided on a substrate.
9. The negative electrode for a secondary battery according to claim 8, wherein The substrate is copper foil.
10. The negative electrode for a secondary battery according to claim 8, wherein it is a negative electrode for a lithium metal secondary battery.
11. The negative electrode for a secondary battery according to claim 10, wherein it is a negative electrode for an anodeless battery.
12. A secondary battery comprising the negative electrode for a secondary battery as described in claim 8.
13. The secondary battery according to claim 12 is a lithium metal secondary battery.
14. The secondary battery according to claim 13 is an anode-free battery.
Citation Information
Patent Citations
High energy density, high power density, high capacity, and room temperature compatible "anode-free" secondary battery
JP2019517722A
Lithium secondary battery
JP2019537226A
